Numerical analysis of line contact elastohydrodynamic lubrication with biobased oils - Osman, Kahar (IEEE Xplore, 2011)
This paper proposes a numerical analysis for elasto hydrodynamic lubrication (EHL) in line contact with vegetable oils as lubricants in order to estimate the pressure profiles and film thickness of EHL. Numerical solution is improved from Houpert and Hamrock's fast approach calculation. The Newton-Raphson method is employed to solve two-dimensional Reynolds equation and Barus' model is used to calculate the viscosity involving the pressure. Vegetable oils were used as lubricants. Results show that sunflower and soybean oil have relatively similar EHL pressure profile and film shape. All tested vegetable oils were able to replace mineral oil as lubricant due to their good pressure profile and film shape. Increasing load and velocity affect the maximum spike pressure and minimum film thickness, where these parameters are increased as increasing load and velocity.